Psychiatric Encounters Madness and Modernity in Yucatan, Mexico - Reyes-Foster, Beatriz M. (Book collections on Project MUSE., 2018)
Psychiatric Encounters presents an intimate portrait of a public inpatient psychiatric facility in the Southeastern state of Yucatan, Mexico. The book explores the experiences of patients and psychiatrists as they navigate the challenges of public psychiatric care in Mexico. While international reports condemning conditions in Mexican psychiatric institutions abound, Psychiatric Encounters considers the large- and small-scale obstacles to quality care encountered by doctors and patients alike as they struggle to live and act like human beings under inhumane conditions. Beatriz Mireya Reyes-Foster closely examines the impact of the Mexican state's neoliberal health reforms on how patients access care and doctors perform their duties. Engaging with madness, modernity, and identity, Psychiatric Encounters considers the enduring role of colonialism in the context of Mexico's troubled contemporary mental health care institutions.